Isolation of Campylobacter jejuni from viscera and bile secretion of broiler chickens with diarrhea - De Carvalho, Angela Cleusa De Fatima Banzatto [UNESP]; Schocken-Iturrino, Ruben Pablo [UNESP]; De Meireles Cama, Luiz Felipe Stelzer Alves [UNESP] (My University, 1997)
Since chickens are important reservoirs of Campylobacter jejuni and their meat is the most frequent route of transmission for human campylobacteriosis, the purpouse of the present study was to investigate the presence of Campylobacter in viscera of chickens with diarrhea, evaluating the frequency of isolation of this microorganism from organs considered to be preferential for its isolation. A total of 107 visceral samples from chickens with diarrhea from different farms in the Ribeirão Preto region, SP, were examined for the presence of Campylobacter jejuni. The material consisted of 73 livers and 34 spleens, plus 29 bile secretion samples. The frequency of Campylobacter jejuni isolation was 54.79% for the liver samples, 35,29% for the spleens and 6,89% for the bile secretion samples. The data suggest that, under the conditions of the present study, the liver may be the organ of choice for the isolation of Campylobacter in the presence of diarrhea and liver involvement in chickens.
Keywords: Broiler chickens; Campylobacter; Diarrhea; Fowl; Viscera